Determination of Groundwater Recharge Area by Using Hydroisotope Technic of Sei Bingei Area and Surrounding Areas, Langkat Regency, North Sumatra - Azmin Nuha; Heru Hendrayana; Agus Budhie Wiyatna; Doni Prakasa Eka Putra; Azwar Satry Muhammad (Journal of Applied Geology, 2020)
Determination of Groundwater Recharge Area by Using Hydroisotope Technic of Sei Bingei Area and Surrounding Areas, Langkat Regency, North Sumatra